Automatic red blood cell counting based on particle area - Musa, Rabiahtuladawiyah (2015)
In medical area, red blood cell (RBC) counting and analysis contributes important information in pathological diagnosis regarding disease such as anemia and low level of hemoglobin concentration. Normally the blood sample is processed in laboratory using hematology analyzer and blood smear is viewed under microscope. The analysis and counting process is conducted manually by pathologist. The task is very laborious, tedious, time-consuming and very dependent to the skill. This project applied image processing techniques to develop a computer-aided system for automated RBC counting. The RBC images will be pre-processed in early stage using morphological operations and thresholding to obtain the images with good quality. Then, the RBC images will be classified based on the particle area size into single and multi-overlap cells. For counting the total number of the RBC, mathematical numeric function is used. The accuracy of the result is determined by doing comparison with the ground truth data. The proposed method has been tested to the RBC images and performs a reliable system for counting RBC.